Comparative analysis of the Spanish and French versions of the treaty called "Family Pact" of 1761 - Luis Mangini (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2018)
This paper offers a comparative analysis of the Spanish and French versions of the Pacte de Famille of 1761, where the mutual military alliance of both crowns of Spain and France are reinforced. The main object of this study aims, firstly, the compared linguistic analysis of this historical document; and secondly, to conclude if it is possible to differentiate a Source Text (ST) and a Target Text (TT). This question is not clarified in the Collection of 1796. Once the political and institutional instrument has been introduced, we proceed to study its structure, specially the organization of its articles. Then, both versions are analyzed from lexical-semantic, syntactic and pragmalinguistic levels. The final conclusions will collect the reflections and reasons about the possible translation, adaptation or parallel writing.